Effects of Justice Theory on Service Recovery Satisfaction on Metro Manila Dine-in Experiences - Tan, Tiffany Adelaine G. (Philippine Management Review; Vol 21 (2014), 2014)
Service failure happens, but as studies have shown, the recovery efforts performed by the frontline employees can turn these negative experiences to satisfying ones. This empirical study investigated how these recovery efforts affect customer satisfaction. The primary objective of the study was to determine how justice theory affects recovery satisfaction. Using confirmatory factor analysis, results showed that distributive and interactional justices have significant effects on recovery satisfaction, while results provided weak support for procedural justice. The effect of distributive justice on recovery satisfaction was stronger than interactional justice. Results also showed that satisfaction with the recovery efforts positively and significantly affect the customer’s behavioral intentions of repurchase and word-of-mouth communications.
Keywords: service failure, service recovery, justice theory, recovery satisfaction, dine-in experiences